Sastra Warna Lokal Betawi Sebagai Bahan Pembelajaran Bahasa Indonesia Untuk Penutur Asing (BIPA) - Ahmad Bahtiar (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: Language related to culture. Like other languages, Indonesian language is also heavily influenced by local cultures. For this reason, as a BIPA teaching strategy, it must also introduce cultures in Indonesia. Materials that can be introduced for this purpose are local color literature in the form of poetry and prose, both novels and short stories. Many local colors in Indonesian literature have been found since the birth of Indonesian literature. In addition to describing the local colors of Minangkabau, various local colors of other regions enrich the Indonesian literary repertoire. The local color literature that can be used is a collection of Terang Bulang Terang di Kali short stories : Keliling Betawi story (2007) by S.M. Ardan. The use of local colors not only introduces Indonesian culture but also increases language skills especially to expand the vocabulary of the Indonesian language. In addition they will enjoy the beauty and capture the message conveyed in the form of the literary work. Thus, teaching BIPA will be fun and useful as well as the function of the literature itself which is dulce et utile, pleasant and useful. Keywords: sastra, warna lokal, strategi pengajaran, BIPA